Invasi Spesies Amphilophus citrinellus Terhadap Ikan Lokal di Perairan Waduk Sanguling - Dadiono, Muh. Sulaiman (Nekton, 2023)
Foreign fish in waters that are not their habitat can have a major impact on the balance of the ecosystem. One of the foreign fish living in Indonesian waters is the red devil foreign fish. The presence of red devil foreign fish (Amphilophus citrinellus) in Indonesian waters reduces biodiversity and is harmful to aquatic ecosystems. This study aimed to assess the negative impact of Amphilophus citrinellus in the Sanguling Reservoir, West Bandung Regency. This study used the desk study method and direct observations in the field. Data were collected using literature review and interview methods. The finding of red devil foreign fish species with the Latin name Amphilophus citrinellus in the Sanguling Reservoir provides information related to the negative impact of invasive foreign fish. This information can be used as a basis for developing regulations that are focused and directed towards invasive species, as well as to increase the active role of several sectors, such as research, and developing mitigation of the impacts caused by invasive species so that the Sanguling Reservoir ecosystem is maintained.